Keefektifan Strategi TPRC (Think, Predict, Read, Connect) Dalam Pembelajaran Membaca Pemahaman Siswa Kelas X SMA Negeri 1 Tangse: The Effectiveness of TPRC (Think, Predict, Read, Connect) Strategy in Reading Comprehension Learning for Grade X Students of SMA Negeri 1 Tangse - Ikram, Fauzan; Rahmi, Hayatun; Nofiana S (Yayasan Sagita Akademia Maju, 2025)
The study titled